Opportunities and Obstacles Associated With Sequential Immune Reconstitution Therapy for Multiple Sclerosis: A Case Report - Garbo, Riccardo; Cutuli, Daniela; Lorenzut, Simone; Gigli, Gian Luigi; Bagatto, Daniele; Valente, Mariarosaria (Frontiers in Neurology, 2021)
Cladribine is an effective disease modifying treatment for relapsing-remitting multiple sclerosis and acts as an immune reconstitution therapy which is administered in a pulsed way. Despite its efficacy, severe disease reactivation early after treatment could represent a serious clinical problem and clear evidence to guide the management of such a situation is lacking. We describe the case of a patient experiencing considerable disease activity during the first year after the initiation of cladribine treatment. The patient was switched to alemtuzumab therapy without receiving the second course of cladribine, which resulted in a better outcome of the disease activity. However, some infectious complications were observed.